Subsidence of the Miyako‐Sone submarine carbonate platform, east of Miyako‐jima Island, northwestern Pacific Ocean. (12th November 2013) - Arai, Kohsaku; Machiyama, Hideaki; Chiyonobu, Shun; Matsuda, Hiroki; Sasaki, Keiichi; Humblet, Marc; Iryu, Yasufumi
Abstract Bathymetric mapping and observations of the seafloor using a remotely operated vehicle (ROV, Hyper‐Dolphin 3K) were carried out on the slopes of the Miyako‐Sone submarine platform, east of Miyako‐jima in the Ryukyu Islands, northwestern Pacific Ocean. The bathymetric map indicates that terraces are present at water depths of approximately 140 m, 330 m, 400 m, and 680 m on the northwestern slope of the platform. A number of NW–SE trending lineaments, probably faults, extend perpendicular to the axis of the Ryukyu Island Arc. Two ROV surveys were conducted at water depths ranging from 519 m (on the slope) to 121 m (shallowest part of the platform). The surveys revealed that well‐indurated carbonate rocks are exposed at terrace margins and on upper slopes, and that the lower slopes are covered with modern sediments consisting of unconsolidated, coarse‐sand‐sized bioclastic carbonates. Calcareous nannofossils from the well‐indurated carbonate rocks indicate a Middle–Late Pleistocene age, which suggests that the rocks correlate with the Quaternary reef and fore‐reef deposits of the Ryukyu Group (Ryukyu Limestone) on the Ryukyu Islands. No siliciclastic deposits corresponding to the upper Miocene–lower Pleistocene Shimajiri Group (as exposed on Okinawa‐jima and Miyako‐jima islands) were recovered during the surveys. Coeval well‐indurated carbonate rocks, all of which formed in a similar sedimentary environment, have been downthrown towards the west due to displacements on the western sides of normal faults. Subsidence of the Miyako‐Sone submarine platform was the result of large vertical displacements on such normal faults. The timing of initial subsidence cannot be tightly constrained, but the presence of the youngest limestone at progressively lower levels towards the west suggests the subsidence continued until after 0.265 Ma.